1984
DOI: 10.1123/apaq.1.3.207
|View full text |Cite
|
Sign up to set email alerts
|

Physical Fitness and Mental Health: A Review of the Literature

Abstract: Empirical evidence has shown a positive relationship between physical training and selected mental health variables. In nonclinical studies the most significant effects of physical exercise have been on self-concept and body image. Two affective variables, depression and anxiety, also seem to be influenced by physical activity but to a lesser degree in this population than with clinical populations. Certain clinical populations appear to benefit cognitively and socially from exercise even though the activity m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…For example, it predicts that the benefits of exercise, in terms of SWB, would be predicted by the extent to which the activity provides a sense of control and is, therefore, enjoyable. This, in turn, links to research showing that enjoyment of sport and exercise is intimately linked to gaining a sense of control via learning new skills (Wankel & Kreisel, 1985) which, if validated, would provide a theoretical understanding for previous reports that programs must be individualised if the participants are to experience maximal involvement, enjoyment and benefit (Tuson et al, 1995;Van Andel & Austin, 1984).…”
Section: The Need For Theorymentioning
confidence: 61%
“…For example, it predicts that the benefits of exercise, in terms of SWB, would be predicted by the extent to which the activity provides a sense of control and is, therefore, enjoyable. This, in turn, links to research showing that enjoyment of sport and exercise is intimately linked to gaining a sense of control via learning new skills (Wankel & Kreisel, 1985) which, if validated, would provide a theoretical understanding for previous reports that programs must be individualised if the participants are to experience maximal involvement, enjoyment and benefit (Tuson et al, 1995;Van Andel & Austin, 1984).…”
Section: The Need For Theorymentioning
confidence: 61%
“…Physical fitness is defined as a set of attributes that people have or achieve while maintaining physical activity (1,2). It is a well-recognised marker of an individual's health status (3)(4)(5). Physical fitness is classified as health-related and skill-related fitness (6).…”
Section: Introductionmentioning
confidence: 99%
“…During this sense, Taekwondo are often seen as a vehicle for developing self-esteem due to its positive effects on psychological state. Recreational and fitness activities are shown to be helpful for various special needs populations [4], Since martial arts practice can have beneficial outcomes, varieties of individuals are looking to the martial arts as a way to treat psychological problems. as an example, [5] found that ladies recovering from psycho-sexual abuse, eating disorders, drug abuse and growing up in dysfunctional families reported that karate training was helpful in their recovery.…”
Section: Introductionmentioning
confidence: 99%